2009
DOI: 10.1002/em.20531
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic genotoxicity of amoxicillin

Abstract: Amoxicillin (AMO), a drug used in the treatment of infections caused by susceptible bacteria, has been evaluated for its ability to induce genotoxicity in human peripheral blood lymphocytes. The potential genotoxic effects of AMO were investigated in vitro by the sister chromatid exchange (SCE), chromosomal aberration (CA), and micronucleus (MN) tests. The cells were treated with 400, 600, 800, and 1,000 microg/ml AMO in the presence and absence of a metabolic activator (S9 mix), respectively. In this study, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…This is also an opportunity to compare the genotoxic risk of DRP in in vivo animals or in another different test system. Previous studies have been shown that β-lactam antibiotics had no genotoxic and cytotoxic effects on human peripheral lymphocytes (19,(45)(46)(47). Likewise, we observed similar results in the present study and the results suggested that DRP caused mutations only at doses much higher than the therapeutic doses.…”
Section: Discussionsupporting
confidence: 92%
“…This is also an opportunity to compare the genotoxic risk of DRP in in vivo animals or in another different test system. Previous studies have been shown that β-lactam antibiotics had no genotoxic and cytotoxic effects on human peripheral lymphocytes (19,(45)(46)(47). Likewise, we observed similar results in the present study and the results suggested that DRP caused mutations only at doses much higher than the therapeutic doses.…”
Section: Discussionsupporting
confidence: 92%
“…Using the sisters chromatid exchange method, mutagenetic and carcinogenic potentials of different substances were examinated [16,17,[20][21][22][23][24][25]. Antibiotics and non-steroidal anti-inflammatory drugs (NSAIDs) were just some of the most investigated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in vitro and vivo deal with different results and conclusions. Xie et al [21] suggest that Tetracycline induce significant increases in SCE even at the lowest concentrations, while, according to Istifli & Topaktaş [20] and Jaju et al [22], Amoxicillin does not behave genotoxic, with recommendation for safe usage in cases of bacterial infections. Also the metabolites of Amoxicillin do not have a significant effect on cell proliferation [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para explicar la no inducción de ICHs luego del tratamiento con ivermectina Estos resultados concuerdan con los observados para otros compuestos, como es el caso del antibiótico amoxicilina, que no incrementa la frecuencia de ICHs en linfocitos humanos cultivados in vitro en presencia o ausencia de un sistema de activación metabólica (Istifli, E.S. y Topaktaş, M., 2010), así como el insecticida propargite en células vegetales in vivo luego del tratamiento con los fungicidas fenarimol e iprodiona (Gadeva, P. y Dimitrov, B., 2008).…”
Section: Análisis Estadísticounclassified